2005
DOI: 10.1016/j.eurpsy.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality of life in first-episode psychosis

Abstract: Quality of life (QoL) measures are increasingly recognized as necessary parts of outcome assessments in psychosis. The present paper is a comprehensive study of patients with first-episode psychosis where QoL is measured by the commonly used Lehman Quality of Life Interview (L-QoLI). The aim is to examine if the L-QoLI maintain its original structure when used in a group of patients with first-episode psychosis, and to investigate what determines global subjective QoL with a specific emphasis on premorbid adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 36 publications
6
37
2
Order By: Relevance
“…On the other hand, clinician-administered rating scales may be subject to difficulties in separating out the influence of prevalent symptoms of the illness, such as negative symptoms (Malla & Payne, 2005). Nevertheless, most studies conclude that self-reported satisfaction or subjective QoL is a valid outcome measure in schizophrenia and other psychotic disorders (Melle et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, clinician-administered rating scales may be subject to difficulties in separating out the influence of prevalent symptoms of the illness, such as negative symptoms (Malla & Payne, 2005). Nevertheless, most studies conclude that self-reported satisfaction or subjective QoL is a valid outcome measure in schizophrenia and other psychotic disorders (Melle et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that QoL is lower in UHR individuals than in the healthy population, and worse than in first-episode psychosis (Bechdolf et al, 2005;Domínguez-Martínez et al, 2015;Ruhrmann et al, 2008). Psychopathological symptoms have been the most commonly studied factors (Górna et al, 2008, Melle et al, 2005, and depressive symptoms have the greatest effect on QoL in both patients with first-episode psychosis and UHR individuals (Ohmuro et al, 2017;Ruhrmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…66 This initiative is in response to the evidence base linking the length of untreated psychosis with reduced quality of life and a worse prognosis 6,47,50 and providing intensive, integrated, sustained outreach-based care during a critical period in the course of illness. 65 Despite reported problems with funding and inequities in access, the number of individuals served by early intervention teams increased from ~1000 to 12,000 between 2002 and 2007.…”
Section: Discussion Of the Economic Evaluationmentioning
confidence: 99%
“…There are widespread problems with social and sexual relationships and in the performance of activities of daily living. 46 A longer duration of untreated psychosis is correlated with a worse QoL, [47][48][49] worse treatment outcome 50 and worse prognosis. 6 QoL tends to be lower where people with psychosis are single, 51 have psychiatric co-morbidity, 51 poor premorbid adjustment, 49 longer duration of psychotic symptoms 49 and poor social relations and finances.…”
Section: Significance Of Psychosis For Patients In Terms Of Ill-healtmentioning
confidence: 99%
“…3,4 A number of clinical factors are linked with diminished QOL including depressive symptoms, [5][6][7][8][9] negative symptoms, [7][8][9] premorbid functioning 6,10 and duration of untreated psychosis (DUP). 6,9 However, findings of the clinical characteristics linked with poorer QOL are not consistently replicated which is predominantly due to methodological variation in QOL definitions and perspectives used. Although consensus seems to have been reached that QOL is a multidimensional construct incorporating assessments of multiple life domains, the perspective from which QOL should be viewed has not been unanimously agreed.…”
Section: Introductionmentioning
confidence: 99%